Pengaruh Motivasi Belajar terhadap Kesulitan Belajar Mahasiswa pada Mata Kuliah Statistik Sosial Prodi Pendidikan Agama Islam - Sulaiman Sulaiman; Firda Dipatia Nurisman (FONDATIA, 2022)
This research was made to decide the impact of motivation on the students’s learning difficulties from the 2018 entry year in the social statistics course, Islamic Education Study Program, UNP. The population of this research were taken from 2018 collague student who entering the Islamic Education Study Program, totaling 170 student, and the sample used was 105 students. The research data was gained from the results of questionnaire that had fulfilled the validity and reliability requirements. Data were interpreted by a simple linear regression technique that composing by T-test, F-test, and Coefficient of Determination. Before testing the hypothesis, the data must go through normality and linearity tests as prerequisite tests. From the proceed of the f-test analysis, it was obtained f count = 52.252 ≥ f table = 3.92, which mean is the learning motivation has an influence to the learning difficulties. Then in the test output from coefficient of determination obtained r2 = 33.7% which indicates learning difficulties are influenced by learning motivation of 33.7% and 62.3% is affected by the other factors. Then the T-test results gained t count = -7.229 <T table = -1.980, meaning that motivation has a significant effect on learning difficulties. The simple linear regression similarity gained is Y = 97,796 – 0,580X which indicates that each learning motivation has increased one value, also learning difficulty reduce by 0.580. Negative sign indicates the existence of a form of influence in the opposite direction. So if learning motivation decreases, learning difficulties will increase. Conversely, if the motivation to learn increases, the difficulty of learning will decrease.